RETORIKA MARAH RUSLI DALAM MEMANG JODOH - Dian Nathalia Inda (Balai Bahasa Kalimantan Barat, 2018)
This study aims to describe the rhetoric that Marah Rusli used in Memang Jodoh. The problem of this research is how is the rhetoric used by Marah Rusli in Memang Jodoh. To solve the problem and the purpose of the study used descriptive qualitative method while the data collection technique used in this study was literature study. The results of the analysis show that the rhetoric used by Marah Rusli is figures of speech, proverb, and imagery. The figures of speech used consist of the metaphorical, personification, hyperbole, repetition, and periphery. The proverb that Marah Rusli uses consist of advice proverb and idioms. While the imagery contained in Memang Jodoh is visual imagery, auditory imagery, motion imagery, and feeling imagery.